Assessing the maintenance of savings sufficiency over the first decade of retirement - Robert Haveman; Karen Holden; Barbara Wolfe; Andrei Romanov (Center for Economic Studies and ifo Institute (CESifo), 2005)
The adequacy of retirement savings is central to the U.S. debate over the effects of Social Security reform and pension changes that would place greater responsibility on individuals for accumulation of retirement resources. We contribute to this discussion by examining the extent to which individuals maintain initial levels of resources over the first decade of retirement. We compare annuitized wealth, including Social Security and pension wealth, to two consumption standards? a household's preretirement earnings and the poverty threshold. We analyze the relationship of individual characteristics to changes in this ratio over time, including the effects of widowhood and post-retirement work.
Keywords: J26; J14; 330; Private Rentenversicherung; Substanzerhaltung; Sparen; Lebensstandard; Alte Menschen; Rentner; USA